ANGLES OF POETIC EXPRESSION IN UZBEK NOVELS OF THE INDEPENDENCE PERIOD (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
The article examines the problem of creative development of national-literary traditions, in particular the literary and artistic heritage of Navoi, which significantly expanded the space-time boundaries of national novels of the period of independence.